Strengthening and sharing capacities for effective and responsible scaling of Cimate-Smart Solutions: Lessons from AICCRA - Ewell, Hanna; Otieno, Felix; Ogutu, Elizabeth (2025)
Scaling climate-smart agriculture and climate information services hinges on capacity development—not only building new skills and institutions, but also sharing proven practices across contexts. Drawing on AICCRA experiences, this InfoNote shows how multi-level capacity—individual, organizational, and systems—advances adoption, financing, and responsible systems change. Five cases illustrate this: farmer field days and demos; training for Climate-Smart Agriculture Investment Plans; agribusiness accelerators; climate-services training with meteorological agencies and universities; and multi-country Scaling Weeks. Emphasizing functional capacities—systems thinking, collaboration, and adaptive management—alongside technical know-how ensures scaling that is inclusive, equitable, and sustainable, strengthening African food systems amid climate uncertainty, at meaningful scale.